Avaliação da presença de alumínio na água do sistema de abastecimento público da cidade de João Pessoa e Grande João Pessoa no estado da Paraíba e os possíveis riscos para a saúde da população - Figueiredo, Gesivaldo Jesus Alves de (2004)
Natural untreated water has high impurity level, containing some innocuous substances but with some components that pose risks to human health, like toxic compounds, bacteria, and viruses. Treatment of water before being consumed by humans is vitally important, because water will become potable and apparently good for consumption after elimination of impurities. The conventional or complete treatment is applied mostly for the water of domestic use, according to standards recommended by the governmental regulation number 518 of 25 March, 2004, of the ministry of health. However, such standard will only be satisfied if the concentration of impurities be limited with respect to the resolution number 20 of 18 June, 1986, adopted by the CONAMA Conselho Nacional do Meio Ambiente (the Brazilian National Council for the Environment). In the present work the potential risks to the human population of João Pessoa, the capital of the State of Paraíba, Northeast Brazil, were evaluated with respect to the concentration of aluminium found in the water supplied by the reservoir system Gramame/Mamuaba. Residues of aluminium in water, generated by aluminium sulphate, may contribute to some illnesses in humans, like osteoporosis, hyperactivity and learning difficulty in children, and even Alzheimer s and Parkinson s diseases. This way, from September 2003 to October 2004, some physical and chemical characteristics of the water, including the concentration of aluminium, were analyzed in untreated and treated waters. The results obtained showed amounts of aluminium above the recommended standards, posing clear risks to consumption of water by human population